Thermoelectric figure of merit of polymeric systems for low-power generators. (11th September 2017) - Cigarini, Luigi; Ruini, Alice; Catellani, Alessandra; Calzolari, Arrigo
Abstract: The request of thermoelectric materials for low-power and flexible applications fosters the investigation of the intrinsic electron and thermal transport of conducting polymeric chains, which are building blocks of the complex variety of organic composites proposed in experimental samples. Using calculations from first principles and the Landauer approach for both electron and phonon carriers, we study the thermoelectric figure of merit zT of three representative and largely used polymer chains, namely poly(3, 4-ethylenedioxythiophene), polyaniline and polyfluorene. Our results provide an upper-limit estimate of zT, due to the intrinsic electronic and vibrational properties of the selected compounds, and pave the way to a microscopic understanding of the mechanisms that affect their electronic and transport characteristics in terms of structural distortions and chemical doping.